1983
DOI: 10.1507/endocrj1954.30.281
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the characteristics of pulsatile LH secretion after estradiol implantation into the preoptic area and the basal hypothalamus in ovariectomized rats.

Abstract: Intracranial actions of estradiol benzoate (EB) in modulating the characteristics of pulsatile LH secretion were examined in ovariectomized rats. A minute amount of crystalline EB was implanted into the medial basal hypothalamus (MBH) or the preoptic suprachiasmatic area (POSC) and blood samples were collected at 6-min intervals for radioimmunoassay of serum LH concentrations. In rats with EB implanted in the MBH, the LH pulse amplitude decreased while the frequency did not change for 3 h after implantation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
1

Year Published

1986
1986
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
1
14
1
Order By: Relevance
“…This suggests that the same central mechanisms do not mediate the negative feedback effects of E2 on both parameters of pulsatile LH release. Moreover, implants of E2 into the medial basal hy pothalamus, but not the MPOA, selectively reduced LH pulse amplitude [2], suggesting that E: may work at differ ent central sites to influence the amplitude and frequency of pulsatile LH release.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This suggests that the same central mechanisms do not mediate the negative feedback effects of E2 on both parameters of pulsatile LH release. Moreover, implants of E2 into the medial basal hy pothalamus, but not the MPOA, selectively reduced LH pulse amplitude [2], suggesting that E: may work at differ ent central sites to influence the amplitude and frequency of pulsatile LH release.…”
Section: Discussionmentioning
confidence: 95%
“…There is a lack of agreement in studies in long-term ovariectomized rats as to whether E2 alters only LH pulse amplitude [20, 21.42], pulse frequency [30], or both parame ters of pulsatile LH secretion [2,44], The present data de monstrate that restoration of DI-D2 or D2-proestrous lev els of E2 1 week after OVX suppressed only LH pulse am plitude, whereas our previous results clearly demonstrated that immediate replacement following OVX with D2-proestrous levels of E2 suppressed both LH pulse amplitude and frequency [28], and immediate replacement with D1-D2 levels of E2 had no influence on pulsatile LH secretion [27], Therefore, D2-proestrous levels of E2 retain their sup pressive action on LH pulse amplitude, and D1-D2 levels of E2 remain ineffective in altering pulse frequency. In con trast, D2-proestrous E2 levels lose their suppressive action on LH pulse frequency, and D1-D2 levels of E2 gain the ability to suppress LH pulse amplitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen administered in the ovariectomized rat initially suppresses luteinizing hormone (LH) secretion, whereas it later induces LH secretory surge EFFECTS ON ARCUATE NEURONS 693 (LEGAN et al, 1975). It is suggested that the initial negative feedback effect is mainly mediated by estrogen responsive neurons in the MBH (AKEMA et a!., 1983(AKEMA et a!., , 1984 as well as by the pituitary gland (BoGDANOVE, 1963). The delayed action, called positive feedback effect, is mediated by neurons in the preoptic region, but not by those in the MBH (KAWAKAMI et al, 1975;KAWAKAMI and KIMURA, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The present study was performed to elucidate how the antidromically identified TI neurons in the arcuate nucleus (ARC), where numerous neuropeptide-and dopamine-containing perikarya have been shown to be present (PALKOVITS, 1982), respond to GABA, glycine, 5-HT, NE, and DA in in vitro preparation of rat hypothalamic slices. The effects of estrogen treatments on the responsiveness of ARC neurons to these agents were also examined, since it has been shown that electrical activity of ARC neurons is affected by estrogen (MAGI, 1973) and that estronge implantation in the ARC causes a change in hormone secretion from the anterior pituitary (AKEMA et al, 1983). A preliminary report of a portion of this study has already been presented (NISHIHARA et al, 1983).…”
mentioning
confidence: 99%